Conductive extracellular matrix derived/chitosan methacrylate/ graphene oxide-pegylated hybrid hydrogel for cell expansion - Jaramillo, Valentina; Arévalo, Daniel Felipe; González-Hernández, Martin; Cortés, María T.; Perdomo-Arciniegas, Ana María; Cruz, Juan C.; Muñoz-Camargo, Carolina (Frontiers in Bioengineering and Biotechnology, 2024)
Electrical stimulation has emerged as a cornerstone technique in the rapidly evolving field of biomedical engineering, particularly within the realms of tissue engineering and regenerative medicine. It facilitates cell growth, proliferation, and differentiation, thereby advancing the development of accurate tissue models and enhancing drug-testing methodologies. Conductive hydrogels, which enable the conduction of microcurrents in 3D in vitro cultures, are central to this advancement. The integration of high-electroconductive nanomaterials, such as graphene oxide (GO), into hydrogels has revolutionized their mechanical and conductivity properties. Here, we introduce a novel electrostimulation assay utilizing a hybrid hydrogel composed of methacryloyl-modified small intestine submucosa (SIS) dECM (SISMA), chitosan methacrylate (ChiMA), and GO-polyethylene glycol (GO-PEG) in a 3D in vitro culture within a hypoxic environment of umbilical cord blood cells (UCBCs). Results not only demonstrate significant cell proliferation within 3D constructs exposed to microcurrents and early growth factors but also highlight the hybrid hydrogel’s physiochemical prowess through comprehensive rheological, morphological, and conductivity analyses. Further experiments will focus on identifying the regulatory pathways of cells subjected to electrical stimulation.